IMPLEMENTASI METODE ENVIRONMENTAL QUALITY ASSESMENT MANAGEMENT (EQAM) DALAM EVALUASI HOLSITIK KAJIAN AMDAL : IMPLEMENTASI METODE ENVIRONMENTAL QUALITY ASSESMENT MANAGEMENT (EQAM) DALAM EVALUASI HOLSITIK KAJIAN AMDAL - M. Farandika Akbar; Muhammad Guntur; Royhan Himawan Putra (Fakultas Teknik Universitas Hamzanwadi, 2025)
Environmental Impact Assessment (EIA) has become a reliable tool in Indonesia for predicting, identifying, and evaluating the potential impacts of an activity. However, despite strong regulations, the implementation of EIA in practice still faces various challenges. The quality of EIA documents is often uneven, influenced by the capacity of the drafters, limitations in baseline data, and limitations in analyzing impacts holistically. In many cases, EIAs tend to use a partial approach in which each impact component is analyzed separately without adequate integration. This prevents EIAs from providing a comprehensive picture of the interactions between environmental components and changes in overall environmental quality. To overcome these shortcomings, a more comprehensive, structured, and quantitative evaluation method is needed. Environmental Quality Assessment Management (EQAM) is one method that offers a more objective evaluation approach through the quantitative indicators and scoring based on the level of importance. In the context of environmental decision-making, the use of EQAM is expected to improve the effectiveness of EIA by producing more in-depth and data-based impact analyses. Based on the results of a case study taken from the EIA of palm oil plantation and crude oil industry activities, it can be seen from the EQAM method that the impact of changes in community perceptions and attitudes is the most affected component, while land acquisition, land preparation and maturation, and industrial operations are the most significant sources of impact. Through this study, it is also possible to conclude the impacts that occur in the same time in order to formulate the areas of concern which can be used as a basis for more effective and comprehensive management and monitoring.